2020
DOI: 10.3847/1538-4357/ab6440
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Detection of Relativistic Image Doubling in Imaging Atmospheric Cherenkov Telescopes

Abstract: Cosmic gamma-ray photons incident on the upper atmosphere create air showers that move to the Earth's surface with superluminal speed, relative to the air. Even though many of these air showers remain superluminal all along their trajectories, the shower's velocity component toward a single Imaging Atmospheric Cherenkov Telescope (IACT) may drop from superluminal to subluminal. When this happens, an IACT that is able to resolve the air shower both in time and angle should be able to document an unusual optical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This quantum foam noise virtual particles as shown [34] exhibits a stochastic Lorentz-Invariance violation where virtual particles can initially and momentarily exceed the speed of light at high sub-Planck energies similar to Cherenkov radiation [37] effect observed by accelerated particles faster than the speed of light inside a medium like water where the speed of light is about one third less than the speed c in the vacuum, and then decelerate into normal luminous speed c and subsequently to subluminous speed inside the medium. Similar as described in the previous referenced study [36], of cosmic-rays penetrating the atmosphere. Due to their initial high momentum, cosmic-rays can penetrate the atmosphere initially with higher speed than the atmospheric speed of light value and then decelerate to lower speed generating an optical effect called Relativistic Image Doubling or RID in short.…”
Section: Quantum Foam and Relativistic Image Doubling Effect Infer To...mentioning
confidence: 64%
See 1 more Smart Citation
“…This quantum foam noise virtual particles as shown [34] exhibits a stochastic Lorentz-Invariance violation where virtual particles can initially and momentarily exceed the speed of light at high sub-Planck energies similar to Cherenkov radiation [37] effect observed by accelerated particles faster than the speed of light inside a medium like water where the speed of light is about one third less than the speed c in the vacuum, and then decelerate into normal luminous speed c and subsequently to subluminous speed inside the medium. Similar as described in the previous referenced study [36], of cosmic-rays penetrating the atmosphere. Due to their initial high momentum, cosmic-rays can penetrate the atmosphere initially with higher speed than the atmospheric speed of light value and then decelerate to lower speed generating an optical effect called Relativistic Image Doubling or RID in short.…”
Section: Quantum Foam and Relativistic Image Doubling Effect Infer To...mentioning
confidence: 64%
“…This omnipresent constant dynamic quantum foam [33] [34] or vacuum noise, pair creation and annihilation can by ansatz of the author herein also interpreted as being superluminous effects as shown similar independently by this recent optical experiments study [35] of the, "Observation of image pair creation and annihilation from superluminal scattering sources", or in this Cosmic-rays study in the atmosphere where the speed of light inside a transparent medium is less than c of the vacuum (e.g. on air) but still superluminal behavior can be observed relative to the predicted speed of light inside this medium in the form of Relativistic Image Doubling effect (RID) [36]. This quantum foam noise virtual particles as shown [34] exhibits a stochastic Lorentz-Invariance violation where virtual particles can initially and momentarily exceed the speed of light at high sub-Planck energies similar to Cherenkov radiation [37] effect observed by accelerated particles faster than the speed of light inside a medium like water where the speed of light is about one third less than the speed c in the vacuum, and then decelerate into normal luminous speed c and subsequently to subluminous speed inside the medium.…”
Section: Quantum Foam and Relativistic Image Doubling Effect Infer To...mentioning
confidence: 85%
“…Possible explanations for temporally symmetrical residuals have been proposed in Hakkila et al (2018) and Hakkila & Nemiroff (2019), which mainly attribute the symmetry to the motion or material distribution of the emitting region. Additionally, it has been shown that superluminal motion may also produce a time-reversed signal (Nemiroff 2018;Nemiroff & Kaushal 2020). Motivated by the reverse-forward shock model from Hakkila & Preece (2014), we suggest that symmetrical or translational signals may be produced by the following process.…”
Section: Indication Of the Grb Scenariomentioning
confidence: 86%